Factors Influencing Rice Farmers' Intention of Smart Farming Technology in Kanigoro Village, Malang Regency - Syifa Aulia; Tri Wahyu Nugroho; Deny Meitasari; Fitria Dina Riana; Moh. Shadiqur Rahman (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
The adoption of smart farming technology among rice farmers in Kanigoro Village, Pagelaran Subdistrict, remains low despite the availability of tools designed to enhance agricultural efficiency. Technologies such as the Smart Soil Sensor and Bird Control Sound System are still underutilized, reflecting a gap between technological availability and farmer adoption. This study analyzes the influence of attitude, subjective norm, and perceived behavioral control on farmers’ intention to adopt smart farming technology, using the Theory of Planned Behavior (TPB) as the analytical framework. A total of 100 farmers were surveyed through structured questionnaires and direct interviews, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all three variables significantly affect intention: attitude (β = 0.19, p = 0.023), subjective norm (β = 0.33, p < 0.001), and perceived behavioral control (β = 0.42, p < 0.001). Perceived behavioral control emerged as the strongest predictor, followed by subjective norm and attitude. These findings highlight that enhancing adoption requires not only promoting positive attitudes but also strengthening social support and improving farmers’ confidence in their ability to access and operate smart farming technologies